L ladin tl sistem formatif Das Ladinische im Bildungssystem : Il ladino nel sistema formativo - Peder Gregori, Gian (bu,press, 2011)
The first volume of the series "Scripta Ladina Brixinensia" edited by Paul Videsott is dedicated to the Ladin language in the educational system - compulsory schools, secondary schools, universities/colleges - in the regions of Trentino-Alto Adige and Friuli as well as in the Canton of Grisons. The focus is on the Ladin department, a unique feature of the Free University of Bolzano, aiming at the documentation, description and the development of the Ladin language. The final contribution presents the volume Sprachen im Vergleich: Deutsch-Ladinisch-Italienisch which is designed as a teaching aid for multilingual language teaching in Ladin schools.